Respuesta :

Answer:

Option 4 which is 1,430.

Step-by-step explanation:

Step 1

In this this step we will break up the terms in the summation symbol using the rules for manipulation summations.

[tex]\sum_{i=1}^{n}(aX^2_i+k)=\sum_{i=1}^{n}(aX)+\sum_{i=1}^{n}k\\\\\sum_{i=1}^{n}(aX^2_i+k)=a\sum_{i=1}^{n}X^2+nk.[/tex]

This means that for our case, the sum can be simplified to be,

[tex]\sum_{i=1}^{11}(3i^2_i-8)=3\sum_{i=1}^{11}i^2+11\times(-8)\\\\\sum_{i=1}^{11}(3i^2_i-8)=3\sum_{i=1}^{11}i^2-88[/tex]

Step 2

In this step we use the formula for the sum of the first n squares to evaluate the first part of the sum in step 2. The formula for the sum of the first n squares is,

[tex]\sum_{i=1}^{n}n^2=\frac{n(n+1)(2n+1)}{6} \\\\\implies\sum_{i=1}^{11}i^2=\frac{11(11+1)(2\times 11+1)}{6} =506[/tex]

Step 3

In this step we use the result from step 1 to evaluate the sum.[tex]3\sum_{i=1}^{11}i^2-88=3(506)-88=1,430.[/tex]

The correct answer is Option 4,which is  1,430.



Answer:

[tex]\boxed{\boxed{\sum_{i=1}^{11}(3i^2-8)=1430}}[/tex]

Step-by-step explanation:

The given expression is,

[tex]\sum_{i=1}^{11}(3i^2-8)[/tex]

[tex]=\sum_{i=1}^{11}(3i^2)-\sum_{i=1}^{11}(8)[/tex]

[tex]=3\sum_{i=1}^{11}(i^2)-\sum_{i=1}^{11}(8)[/tex]

we know that,

[tex]\sum_{i=1}^{n}i^2=\dfrac{n(n+1)(2n+1)}{6}[/tex] and

[tex]\sum_{i=1}^{n}c=cn,\text{ Where c is a constant}[/tex]

Hence,

[tex]3\sum_{i=1}^{11}(i^2)-\sum_{i=1}^{11}(8)=3\left(\dfrac{11(11+1)(2(11)+1)}{6}\right)-8(11)[/tex]

[tex]=3\left(\dfrac{11(12)(23)}{6}\right)-8(11)[/tex]

[tex]=3\left(506}\right)-8(11)[/tex]

[tex]=1518-88[/tex]

[tex]=1430[/tex]